2003
DOI: 10.1002/joc.924
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of techniques for detection of discontinuities in temperature series

Abstract: Several techniques for the detection of discontinuities in temperature series are evaluated. Eight homogenization techniques were compared using simulated datasets reproducing a vast range of possible situations. The simulated data represent homogeneous series and series having one or more steps. Although the majority of the techniques considered in this study perform very well, two methods seem to work slightly better than the others: the standard normal homogeneity test without trend, and the multiple linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
142
1
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(155 citation statements)
references
References 11 publications
3
142
1
8
Order By: Relevance
“…This calls for sequential tests where the existence of a regime shift is tested for at every point in time, and which must be characterized by higher critical values of the test statistic than in classical statistical methods (cf. Box 2) due to the so-called The most commonly investigated regime shift hypothesis is a step change in mean level using parametric [40,42,43] development of threshold detection methods in econometrics and climate research (often > 100 time steps). As change-points occurring at the extremes of a time series do not lend much power to hypothesis testing, it is only those change-points located near the middle of the time series that can be detected with confidence.…”
Section: Inferential Statistics and Hypothesis Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…This calls for sequential tests where the existence of a regime shift is tested for at every point in time, and which must be characterized by higher critical values of the test statistic than in classical statistical methods (cf. Box 2) due to the so-called The most commonly investigated regime shift hypothesis is a step change in mean level using parametric [40,42,43] development of threshold detection methods in econometrics and climate research (often > 100 time steps). As change-points occurring at the extremes of a time series do not lend much power to hypothesis testing, it is only those change-points located near the middle of the time series that can be detected with confidence.…”
Section: Inferential Statistics and Hypothesis Testingmentioning
confidence: 99%
“…This calls for sequential tests where the existence of a regime shift is tested for at every point in time, and which must be characterized by higher critical values of the test statistic than in classical statistical methods (cf. Box 2) Critical values at different significance levels are tabularized for regularly observed data points, typically time series [38] The most commonly investigated regime shift hypothesis is a step change in mean level using parametric [40,42,43] or non-parametric [44] methods. Regime shift detection methods involving changing variance, shift in the frequencies of fluctuations, or even simultaneous interrelated shifts in several ecosystem components at a particular point have also been proposed [45], but their application to practical data analysis has so far been limited.…”
Section: Inferential Statistics and Hypothesis Testingmentioning
confidence: 99%
“…Buishand (1982) and Peterson et al (1998a, b)havediscussed in detail the application of relative and absolute tests. Detailed mathematical development of the tests is also discussed in Wijngaard et al (2003), while Ducré-Robitaille et al (2003) provides a comparison between the techniques.…”
Section: Homogeneity Testingmentioning
confidence: 99%
“…Alexandersson (1986) developed the 'Standard normal homogeneity test' (SNHT), applied to the Swedish precipitation series in subsequent work Moberg and Alexandersson, 1997). The SNHT is one of the most efficient tests for homogeneity, as Ducré-Robitaille et al (2003) recently demonstrated.…”
Section: Introductionmentioning
confidence: 99%